2023
DOI: 10.1097/ijg.0000000000002210
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Partial Versus Complete Goniotomy With or Without Phacoemulsification for Primary Open Angle Glaucoma: A Multicenter Study

Abstract: Précis: Goniotomy (GT) 120 degrees with or without phacoemulsification was sufficient to lower the intraocular pressure (IOP) and reduce hyphema for primary open angle glaucoma. Purpose: To compare the surgical outcomes and safety profiles of 120 degrees and 360 degrees GT with or without phacoemulsification cataract extraction and intraocular lens implantation (PEI) for primary open angle glaucoma. Patients and Methods: This multicenter retrospective study consisted of 139 eyes and was divided into 4 grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Postoperative layered hyphema was more frequently reported with a 360-degree incision compared to a 180-degree incision in GATT procedures [9]. Similarly, the incidence of hyphema was more common following goniotomy with a 360-degree incision than with a 120-degree incision [12,13]. In our previous research, we reported higher hyphema scores in eyes undergoing TMH than in those receiving first-and secondgeneration iStent implants during the early postoperative period [19,29].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Postoperative layered hyphema was more frequently reported with a 360-degree incision compared to a 180-degree incision in GATT procedures [9]. Similarly, the incidence of hyphema was more common following goniotomy with a 360-degree incision than with a 120-degree incision [12,13]. In our previous research, we reported higher hyphema scores in eyes undergoing TMH than in those receiving first-and secondgeneration iStent implants during the early postoperative period [19,29].…”
Section: Discussionmentioning
confidence: 67%
“…Studies on cadaver eyes suggested that the extent of trabeculotomy incision influences IOP reduction [4]. While some studies reported varying IOP reduction efficacy based on the width of the surgical extent [5][6][7], others found no such differences [8][9][10][11][12][13]. Assessments of the correlation between surgical extent and IOP reduction efficacy often involved comparing different surgical procedures or groups with varying preoperative IOP or patient backgrounds [5][6][7]10,13].…”
Section: Introductionmentioning
confidence: 99%
“… 6 In another study, Song et al also found no significant difference in IOP reduction when performing goniotomy on 120 vs 360 degrees with or without phacoemulsification (Tanito Microhook or KDB for the 120 degree goniotomy and GATT for 360 degrees). 7 Similarly, Hughes et al found no difference in IOP reduction at 18 months in eyes treated with 180 or 360 degrees of canaloplasty using the Visco360 or OMNI device. 8 While further research is needed to delineate these outcomes, the potentially varying regions being targeted in these studies may be at least partially responsible for these results.…”
Section: Discussionmentioning
confidence: 95%
“… 4 , 5 Lastly, treating more than 180 degrees may increase the risk of post-operative complications, such as hyphema and inflammation, which could lead to less favorable outcomes or more complicated post-operative recovery periods. 7 , 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation